Urbanization of Muslim Community in India—A Metaphor for Development? Evidences from States of West Bengal and Kerala - Saurav Chakraborty; Saswata Ghosh & Subhanil Chowdhury
Historically, the religious affiliation of urbanization in India has always rendered a relative advantage for Muslim Community. During 2000–2011, in situ urbanization process has strengthened this popular belief. This trend is more pronounced in the states of Kerala and West Bengal, perhaps due to the colossal escalation of new Census Towns (CTs). This present study is an endeavour to understand whether recent upsurge of urbanization among Muslims in India can be linked with “devel- opment” in these two states based on availabilities of Basic Urban Infrastructures (BUIs), principally in the new CTs. This has been done by employing an “availability index” of infrastructures by obtaining data from Village Directory of West Bengal and Kerala, Census of India. The BUIs include educational and health institutions, bus and railway services and drinking water facility. Most importantly, where these amenities were absent in 2001, the distance travelled by the inhabitants, to get access to these services has also been examined here. The study concludes through extending the debate on whether an increase in the number of population, particularly of Muslim community, in urban areas can be taken as a true signature of development or not.